URGENSI DIMENSI ETIS PESAN AL-QUR’AN DALAM PENGEMBANGAN HUKUM ISLAM (UINSI Samarinda, 2015)
This article tries to reveal the ethical dimension of the urgency message of the Qur'an in the development of Islamic law, especially in relation to dealing with global issues today. Islamic Jurisprudence (Fiqh), as a discipline of Islamic law must be able to answer the problems of humanity in a